Topological Bistability of the π-System in a Helicene Carbon Nanohoop - Malinčík, Juraj; Šolomek, Tomáš (Synlett, 2024)
Molecules with a π-system that can be mapped onto a Möbius strip may display Möbius aromaticity. Such molecules are difficult to synthesize because they have a twisted structure. Recently, we combined chiral [6]helicene and fluorescent [7]cycloparaphenylene, and synthesized the first helicene para-phenylene ([6,7]HPP) carbon nanohoop. We have demonstrated that this design strategy ultimately provides a Möbius topology of the molecular π-electron system and, therefore, offers the potential to study Möbius aromaticity experimentally. In addition, the synthesized nanohoop exists as a mixture of conformers in solution. Some of the conformers possess a different orientability of their π-systems, i.e., they differ in their topology. As a result, the recorded circularly polarized luminescence of isolated enantiomers displays both left- and right-handedness of the emitted light, each emanating from a conformer with a different π-system topology. Therefore, [6,7]HPP provided the first experimental evidence of such topological bistability in carbon nanohoops.
Keywords: circularly polarized luminescence; Möbius aromaticity; molecular topology; carbon nanohoops; cycloparaphenylenes; helicenes